Perancangan Aplikasi Pembayaran Kwh Listrik Pascabayar Berbasis Web Pada Gedung Bertingkat (Apertement The Mansion Bougenville) - Prasetya, Dimas; Junaedi, Ifan; Yulianto, Akmal Budi (STIKOM Tunas Bangsa Pematangsiantar, 2025)
This research focuses on the design and development of a web-based postpaid electricity payment application for high-rise buildings, specifically for residents of The Mansion Bougenville Apartment. The aim of this application is to simplify and streamline the process of paying electricity bills by automating the calculation of power consumption and enabling online payments. The application allows residents to input their monthly KWH usage, calculates the corresponding bill based on the applicable tariff, and offers various payment methods, such as bank transfers and e-wallets. This system not only reduces errors in manual calculations but also improves the overall efficiency of payment processing by enabling real-time transactions. All payment data is securely stored in the system, providing both transparency and easy access to transaction records for residents and building management. The results of the implementation show that the web-based application has significantly increased the convenience, accuracy, and efficiency of electricity payments for residents of The Mansion Bougenville Apartment, offering an improved alternative to traditional manual payment systems.